Застосування статистичних методів при вибіркових спостереженнях в аудиті - Іваніна, О.О. (Культура народов Причерноморья, 2013)
У статті розглянуто особливості застосування статистичних і нестатистичних
вибіркових спостережень в аудиті фінансової звітності. Проаналізовані основні технології вибіркового
аудита, детально розглянуто метод якісного вибіркового дослідженн. Досліджено порядок формування
аудиторської вибірки за допомогою статистичних методів спрямованих на визначення її обсягів і
кінцевих результатів. В статье рассмотрени особенности применения статистических и нестатистических
выборочных наблюдений в целях аудита финансовой отчетности. Проанализированы основные
технологии выборочного аудита, детально рассмотрен метод качественного выборочного
исследования. Исследован порядок формирования аудиторской выборки с помощью статистических
методов направленных на определение ее объемов и конечных результатов. In article features of application of statistical and nonstatistical elective supervision with a view of
audit of accounting are considered. The phases of elective research with the use of monetary sample and
qualitative elective research are considered. Their advantages and deficiencies are investigated.
Attention on expediency of application of qualitative elective research with a view of audit of accounting is
stressed. The main technologies of elective audit are analysed, in detail method of qualitative elective research is
considered which is of interest for the evaluation of reliability of the system of inside control of the Companycustomer.
Order of formation of auditory sample with the aid of statistical methods of volumes and results
directed to definition of it is investigated. Order of establishing of admissible deviations norm, establishing of
admissible risk of maximum trust, the evaluation of deviation of set norms is considered.
Order of definition of volumes of sample for qualitative elective research is considered at the risk of maximum
trust of equal to five per cent. The formula is presented which allows revising volume of sample, if it exceeds 10
% sent. After updating of initial volume of sample units from set are selected. As qualitative elective research
represents a probability method, necessary is noted to produce selection by random way. Following which it is
necessary to conduct auditory procedures on check of choosing documents.